Accuracy Assessment of Digital Surface Models Based on a Small Format Action Camera in a North-East Hungarian Sample Area - Barkóczi, Norbert; Szabó, Gergely (Geographica Pannonica, 2017)
The use of the small format digital action cameras has been increased in the past few years in various applications, due to their low budget cost, flexibility and reliability. We can mount these small cameras on several devices, like unmanned air vehicles (UAV) and create 3D models with photogrammetric technique. Either creating or receiving these kind of databases, one of the most important questions will always be that how accurate these systems are, what the accuracy that can be achieved is. We gathered the overlapping images, created point clouds, and then we generated 21 different digital surface models (DSM). The differences based on the number of images we used in each model, and on the flight height. We repeated the flights three times, to compare the same models with each other. Besides, we measured 129 reference points with RTK-GPS, to compare the height differences with the extracted cell values from each DSM. The results showed that higher flight height has lower errors, and the optimal air base distance is one fourth of the flying height in both cases. The lowest median was 0.08 meter, at the 180 meter flight, 50 meter air base distance model. Raising the number of images does not increase the overall accuracy. The connection between the amount of error and distance from the nearest GCP is not linear in every case.